Pengaruh Latihan Menggunakan Hand Paddle Dan Fins Terhadap Kecepatan Renang Gaya Bebas Pada Atlet Pemula Di Club Btp Aquatic Kota Bengkulu - Agnes Putri Chairunnisa (UNIVED Press, Universitas Dehasen Bengkulu, 2026)
This study aims to determine the effect of training using hand paddle and fins on the freestyle swimming speed of beginner athletes at the BTP Aquatic Club in Bengkulu City. This research employed an experimental method with a one-group pretest-posttest design, without a control group. The research sample consisted of 20 beginner athletes selected through purposive sampling. Data collection techniques involved a 25-meter freestyle swimming speed test conducted before and after the treatment (training using hand paddle and fins). The data analysis using a t-test showed a significant difference between the pretest and posttest results, with a t-value of 3.905 and a t-table value of 1.734 (at a 0.05 significance level). The average freestyle swimming time before the treatment was 20.25 seconds, and after the treatment it improved to 16.7 seconds, indicating a significant increase in speed. The conclusion of this study is that training using hand paddles and fins significantly improves freestyle swimming speed among beginner athletes. This study recommends that coaches and swimming clubs incorporate these tools into training programs to enhance beginner athletes' swimming performance.